A Colorimetric and Long‐Wavelength "Turn‐On" Fluorescent Probe for Copper Ions Detection with High Selectivity and Sensitivity. Issue 25 (5th July 2021) - Zeng, Xiaodan; Gao, Song; Jiang, Cheng; Jin, Xing; Ma, Mingshuo; Liu, Zhigang; Chen, Jie
Abstract: In this paper, a seminaphthorhodafluor‐based colorimetric and fluorescent probe with the picolinate moiety as a recognition receptor was designed and simply synthesized by a one‐step reaction. The probe was utilized as a long‐wavelength "turn‐on" fluorescent indicator for Cu 2+ with high selectivity in the aqueous solution. In addition, the color of probe solution changed from nearly colorless to purple in the presence of Cu 2+, and thus the probe could be used as a colorimetric indicator for Cu 2+ . Furthermore, the linear detection range of Cu 2+ was 0–2 μM and the limit of detection (LOD) for detecting Cu 2+ was calculated to be 52 nM. These results suggest that this probe has high sensitivity toward Cu 2+ . Importantly, this probe has been successfully applied to detect Cu 2+ in real water samples. Also, the probe can image intracellular Cu 2+ through laser confocal fluorescence microscope. Abstract : A new highly selective and sensitive "turn‐on" fluorescent probe for Cu 2+ was synthesized. It is obvious that the fluorescence intensity of probe‐ Cu 2+ is much stronger than that of the probe itself. So, a simple and colorimetric method for detection of Cu 2+ was developed. This probe could be successfully applied to real water samples and live cells and showed its excellent practicability.